Therapeutic Potential of Synthetic Human β-Defensin 1 Short Motif Pep-B on Lipopolysaccharide-Stimulated Human Dental Pulp Stem Cells - Shi, Jue; Hu, Zihe; Zhou, Yanyan; Zuo, Minghao; Wu, Haiyan; Jin, Wenjing; Xie, Zhijian (Mediators of Inflammation, 2022)
Dental pulp inflammation is a widespread public problem usually caused by caries or trauma. Alleviating inflammation is critical to inflamed pulp repair. Human β-defensin 1 short motif Pep-B is a cationic peptide that has anti-inflammatory, antibacterial, and immunoregulation properties, but its repair effect on human dental pulp stem cells (hDPSCs) under inflammation remains unclear. In this study, we aimed to investigate anti-inflammatory function of Pep-B and explore its therapeutic potential in lipopolysaccharide-(LPS-) induced hDPSCs. CCK-8 assay and transwell assay evaluated effects of Pep-B on hDPSC proliferation and chemotaxis. Inflammatory response in hDPSCs was induced by LPS; after Pep-B application, lactate dehydrogenase release, intracellular ROS, inflammatory factor genes expression and possible signaling pathway were measured. Then, osteo-/odontoblast differentiation effect of Pep-B on LPS-induced hDPSCs was detected. The results showed that Pep-B promoted hDPSC proliferation and reduced LPS-induced proinflammatory marker expression, and western blot result indicated that Pep-B inhibited inflammatory activation mediated by NF-κB and MAPK pathways. Pep-B also enhanced the expression of the osteo-/odontogenic genes and proteins, alkaline phosphatase activity, and nodule mineralization in LPS-stimulated hDPSCs. These findings indicate that Pep-B has anti-inflammatory activity and promote osteo-/odontoblastic differentiation in LPS-induced inflammatory environment and may have a potential role of hDPSCs for repair and regeneration.